Drug Administrations for Patients Improves Hematologic Values in Fighting COVID-19 at Private Hospital in Jakarta, Indonesia - Arief, Ilham (International Journal of Scientific Research and Management (IJSRM), 2021)
No specific drugs have been found for the COVID-19 pandemic until now. The drug administration follows the national standards imposed to prevent the worsening of the patient's condition in the hope of recovery. The purpose of this study was to look at the effect of drug administration on hematologic parameters before and after the administration of drugs. This research method is cohort-based observational with the collection of retrospective medical record data from March to October 2020 at the Central Jakarta Private Hospital, Indonesia. The results showed improvement values in hematologic parameter values in eosinophils, neutrophils, monocytes, and neutrophil-lymphocyte ratios, and statistically, the parameter of eosinophils values is a significant difference after administering the drug.